2007 IEEE Conference on Emerging Technologies &Amp; Factory Automation (EFTA 2007) 2007
DOI: 10.1109/efta.2007.4416815
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the impact of vertical integration on response times in ethernet fieldbuses

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 13 publications
1
17
0
5
Order By: Relevance
“…However, results obtained by measurements (Denis et al [2007]) on this kind of architecture showed that, in spite of this complexity, the load of the fieldbus does not impact the transmission delays. Thus, for the communication between two components, the network can be assumed perfect (no limit of throughput, no congestion) and modelled as a constant delay.…”
Section: Networkmentioning
confidence: 99%
“…However, results obtained by measurements (Denis et al [2007]) on this kind of architecture showed that, in spite of this complexity, the load of the fieldbus does not impact the transmission delays. Thus, for the communication between two components, the network can be assumed perfect (no limit of throughput, no congestion) and modelled as a constant delay.…”
Section: Networkmentioning
confidence: 99%
“…Such assumptions are often taken for granted in the context of NAS [11], as is the case in our study, for two main reasons: -The exchanged data packets are of a short length, and just a few bytes are sufficient to transmit data. With Modbus for instance, the request can reach up to 256 bytes only [2].…”
Section: Timed Event Graphs and Max-plus Algebramentioning
confidence: 99%
“…As a matter of fact, the PLC modules are not synchronized and RIOMs may be shared across many applications, which leads to delays that must then be incorporated. To the best of our knowledge, studies that consider the entire architecture (both field devices and the network) are still quite rare and often informally based on case simulation or experimental measurements targeting a limited number of systems [10], [11]. The only formal method developed has been based on model-checking [12] aiming to check if a timing property holds or not.…”
Section: Introductionmentioning
confidence: 99%
“…The three steps of this strategy, that might be automated, will be sketched in this section and are explained with more details in Ruel et al (2008). (Marsal (2006) and Denis et al (2007)); then, the duration of an exchange between one PLC and one RIOM does not depend on the other exchanges.…”
Section: Modelling the Automation Systemmentioning
confidence: 99%
“…Nevertheless, it matters to avoid synchronization between the input signal and the IOscanning cycle to prevent from meaningless measures. Then the frequency of the input signal must be set as explained in Denis et al (2007).…”
Section: Fig 3 Response Time Measurementmentioning
confidence: 99%